2014
DOI: 10.1016/j.resuscitation.2013.12.008
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes associated with amiodarone and lidocaine in the treatment of in-hospital pediatric cardiac arrest with pulseless ventricular tachycardia or ventricular fibrillation

Abstract: Aim To determine the association between amiodarone and lidocaine and outcomes in children with cardiac arrest with pulse less ventricular tachycardia (pVT) and ventricular fibrillation (VF). Background Current AHA guidelines for CPR and emergency cardiovascular care recommend amiodarone for cardiac arrest in children associated with shock refractory pVT/VF, based on a single pediatric study and extrapolation from adult data. Methods Retrospective cohort study from the Get With the Guidelines-Resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 19 publications
(26 reference statements)
0
34
0
4
Order By: Relevance
“…For the important outcome of ROSC, there was very-lowquality evidence (downgraded for risk of bias, imprecision, indirectness, and possible publication bias) from 1 observational cohort study of pediatric IHCA 62 showing improved ROSC associated with lidocaine use when compared with amiodarone use (50.9% [87/171], ROSC in the amiodarone group and 62.4% [184/295] in the lidocaine group; P=0.002). Use of lidocaine, compared with no lidocaine use, was significantly associated with an increased likelihood of ROSC (aOR, 2.02; 95% CI, 1.36-3).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For the important outcome of ROSC, there was very-lowquality evidence (downgraded for risk of bias, imprecision, indirectness, and possible publication bias) from 1 observational cohort study of pediatric IHCA 62 showing improved ROSC associated with lidocaine use when compared with amiodarone use (50.9% [87/171], ROSC in the amiodarone group and 62.4% [184/295] in the lidocaine group; P=0.002). Use of lidocaine, compared with no lidocaine use, was significantly associated with an increased likelihood of ROSC (aOR, 2.02; 95% CI, 1.36-3).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…25 Observational data support the use of ECPR for infants and children in cardiac arrest (especially those with underlying cardiac disease) in the in-hospital critical care setting, when patients are refractory to conventional resuscitation, and when the necessary ECPR protocols, expertise, and equipment exist. 26,27 No evidence exists to support its routine use for cardiac arrest in the out-of-hospital setting.…”
Section: Intra-arrestmentioning
confidence: 97%
“…This recommendation was based predominantly on a paediatric case series (65) and extrapolation from adult studies that used short-term outcomes. (66) Valdes et al (67) recently reported that, in their observational cohort study, the use of lignocaine was associated with an increased likelihood of ROSC, as compared with the use of amiodarone or without the use of lignocaine. However, the same study did not show an association between lignocaine or amiodarone use and survival to hospital discharge.…”
Section: (B) Medicationsmentioning
confidence: 99%